Pengaruh Religiusitas Terhadap Minat Masyarakat Menggunakan Produk Perbankan Syariah di Kota Bandar Lampung - Hakim, Faqih Wildan; Hasan, Ashari; Putra, Irhamsyah (Al-Mashrof: Islamic Banking and Finance, 2022)
This study aims to determine the effect of religiosity on people's interest in using Islamic Bank products in the city of Bandar Lampung. The sample in this study used purposive sampling technique. The data used in this study are primary data obtained through questionnaires distributed to the public or prospective customers of Bank Syariah Mandiri in Bandar Lampung city. Based on a sample of 100 respondents using simple regression analysis, it shows that the religiosity variable can affect people's interest in using Islamic bank products by 15.3%. With the results of the analysis showing that the religiosity variable has a significance value of 0.000, it means that the religiosity variable has a positive and significant influence on people's interest in using Islamic bank products. These results provide an opportunity for Bank Syariah Mandiri to increase the socialization of Islamic bank products to the public. Because, with increasing religiosity, the tendency of people to be interested in using Islamic bank products is increasing.